Model Pelaporan Keuangan Perguruan Tinggi Muhammadiyah Aisyiyah (PTMA) - Siswadi Sululing; Arisanjaya Doloan (Jurnal Proaksi, 2024)
PTMA financial reporting standards are not yet uniform. The purpose of this study was to determine the financial reporting model used by PTMA. The financial reporting of universities in Indonesia is different, public universities are based on government regulations and financial accounting standards (SAK). PTMA is based on the PTMA financial management system guide and SAK. PTMA prepares financial reports based on financial management system guidelines, SAK Entities Without Public Accountants (ETAP), and Interpretation of Financial Accounting Standards (ISAK) 35. This research was conducted at 14 PTMAs. The data collection method used was questionnaires and documents through searching the available PTMA website. The data analysis method used is content analysis. The results of the study are that there are 3 financial reporting models applied by PTMA base on: 1).PTMA Financial Management System Guidelines, 2). SAK ETAP, and 3). SAK ISAK 35.